PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT BIGGY CEMERLANG JAKARTA UTARA - Dwi Ismiyati; Endang Kustini (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine the influence of organizational culture and work discipline on employee performance at PT. Biggy Cemerlang North Jakarta both partially and simultaneously. The study was conducted on employees of PT. Biggy Cemerlang North Jakarta, with an employee population of 90 people. The sampling technique used in this study is saturated sampling, data analysis techniques using validity tests, reliability tests, classical assumption tests, regression analysis, determination analysis and hypothesis testing. The results of the study indicate that partially Organizational Culture (X1) influences Employee Performance (Y) with a calculated t value> t table or (3.803> 1.9872). Partially, Work Discipline (X2) influences Employee Performance (Y) with a calculated t value> t table or (3.803> 1.9872). And together, organizational culture and work discipline have a significant influence on company performance. Based on the calculated f value> f table or (92.355> 3.10).